A POLICY EVALUATION ON LAND PROCUREMENT USED FOR NATIONAL ROAD SPREADING IN BANGKA TENGAH REGENCY, KEPULAUAN BANGKA BELITUNG PROVINCE - Retno Negoro, Wijaya Sukarno (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
The policy of national land procurement is formed under a national consensus which states that land procurement in Indonesia must be implemented by emphasizing the principles of the Indonesian constitution and land law. In terms of land procurement, the local government of Bangka Tengah has a different policy from the national policy. In Bangka Tengah, land values are not included in the calculation of compensation value for the land acquisition. The compensation is only accounted for buildings, crops and other measurable losses. The study attempts to identify the concepts implemented by the local government of Bangka Belitung on their land procurement policy and to describe the conformity of the policy with the national policy under the Indonesian law no. 2 year 2012 No. 2 on Land Procurement for public facilities development. In evaluating the data, Dunn evaluation method is employed. Â The method is a formal evaluation that focuses on the conformity in land procurement with the national constitution no 2. year 2012. The study indicates that substantially the land procurement policy implemented in Bangka Tengah is not in contradiction to the national land procurement policy. However, in the future, this kind of local policy will be more difficult to be put into effect.